DIRASAH EL-BADR : STRATEGI PENGUATAN TRADISI KEILMUAN ASATIDZ PESANTREN PERSIS AL-ASMA SUMEDANG - Saefullah, Agus Susilo (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This research aims to explore strategies for strengthening scientific traditions among the Asatidz of the Persis Al-Asma Sumedang Islamic Boarding School through the Dirasah El-Badr program. A descriptive qualitative approach was used in this research to understand the dynamics and effectiveness of the strategies implemented in the program. Data was collected through in-depth interviews with Asatidz, participatory observation during program implementation, as well as analysis of related documents. The research results show that Dirasah El-Badr is important in improving Asatidz's scientific competence through a comprehensive and continuous learning approach. This program strengthens scientific traditions because Asatidz are conditioned to continue learning by studying various Islamic literature and are used to writing thought constructions and discussing by arguing while still prioritizing adab. The challenges faced include limited resources, a busy schedule of activities, and the need to increase the number of libraries (maraji) in the form of classical books and books on contemporary Islamic studies. This research suggests increasing supporting facilities, increasing time allocation for scientific activities, and literature (maraji) in the form of classical Islamic books and books on contemporary Islamic studies. It is hoped that the findings of this research can provide practical guidance for other Islamic boarding schools that wish to strengthen scientific traditions among Asatidz.